Method for evaluating moisture absorption reaction degree of low-NCO reactive polyurethane
By hygroscopic reaction of low NCO-reactive polyurethane and water vapor, the relationship between the degree of hygroscopic reaction and infrared absorbance is established, and the problem that the prior art cannot effectively evaluate the degree of hygroscopic reaction of low NCO-reactive polyurethane is solved, and efficient quality control of this type of polymer is achieved.
Patent Information
- Application Number
- CN202311170165.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art cannot effectively evaluate the degree of hygroscopic reaction of low-NCO-reactive polyurethane, which makes it difficult to control product quality.
By hygroscopic reaction of low NCO-reactive polyurethane with known isocyanate mass content and water vapor, standard products with different levels of hygroscopic reactions were obtained, and the absorbance of characteristic functional groups of the standard was detected by infrared spectroscopy, and the relationship between the degree of hygroscopic reaction and the absorbance was established, and the degree of hygroscopic reaction of the sample to be tested was evaluated.
It realizes efficient monitoring and evaluation of the degree of hygroscopic reaction of low NCO-reactive polyurethane, provides an important basis for product quality control, and solves the problem that liquid water is difficult to disperse evenly in the sample.
Smart Images

Figure CN119595579A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of quality control of low NCO reactive polyurethane, and in particular relates to a method for evaluating the degree of moisture absorption reaction of low NCO reactive polyurethane. Background Art
[0002] Low NCO reactive polyurethane, also known as moisture-curing polyurethane, is a product of isocyanate modified by alcohol or amine. It has become a research hotspot in the adhesive field in recent years due to its green and environmentally friendly, excellent performance and wide application. When used, low NCO reactive polyurethane needs to be applied to the substrate and then undergo moisture-curing cross-linking reaction. When the product is exposed to the air for a long time, it reacts with moisture in the air, causing increased viscosity and even agglomeration, affecting the use of the product.
[0003] Therefore, for the application field of low NCO reactive polyurethane, the degree of moisture absorption of the product is a very important indicator, which has a great impact on practical application. If the degree of moisture absorption is not understood accurately, it will cause serious losses to actual production. The isocyanate content of low NCO reactive polyurethane is low, generally 1-3%, and the mass change is very small when reacting with water, and it cannot be characterized by the balance weighing method. At present, there is no suitable evaluation method for how many isocyanate groups in low NCO reactive polyurethane products react with water, that is, the degree of product failure.
[0004] Chinese patent application CN107703096A discloses a method for detecting the content of water and / or urea in isocyanate and its application for online monitoring, using a near infrared method to test urea in isocyanate, wherein the isocyanate is MDI, TDI, PM, IPDI, etc. However, these products are not modified by alcohol or amine, the isocyanate content is also more than 30%, and the water content is 0.001wt%-0.1wt%. These products have great differences in structure and viscosity from low NCO reactive polyurethane, and there are great differences in material state, so this method cannot be used as a reference.
[0005] In the study on the hygroscopic mechanism of MDI, Liu Hairong et al. characterized the hygroscopic degree of MDI by the balance weighing method, and characterized the hydrogen bonding of urea bonds by the FTIR infrared spectrometer. The test samples were also unmodified isocyanates with isocyanate contents of more than 30%, which was quite different from the low NCO reactive polyurethane structure and the material state, so the methods could not be used as a reference.
[0006] In the study of the synthesis of polyurethane adhesives and the hygroscopicity of the bonded bodies, Wen Ling et al. investigated the hygroscopic properties of the products after the polyurethane prepolymers were cured by adding ethylene glycol and ammonium nitrate. This method is also not suitable for evaluating the degree of hygroscopic reaction of low NCO reactive polyurethanes.
[0007] Therefore, it is necessary to develop a method suitable for evaluating the degree of moisture absorption reaction of low NCO reactive polyurethane. Summary of the invention
[0008] The invention provides a method for evaluating the degree of hygroscopic reaction of a low NCO reactive polyurethane. The method is advantageous for efficiently monitoring the degree of hygroscopic reaction of the low NCO reactive polyurethane and for conveniently and quickly evaluating the product quality of the low NCO reactive polyurethane.
[0009] To achieve the purpose, the present invention provides the following technical solutions:
[0010] The present invention provides a method for evaluating the degree of moisture absorption reaction of low NCO reactive polyurethane, the method comprising the following steps:
[0011] (1) subjecting a low-NCO reactive polyurethane having a known isocyanate mass content to a hygroscopic reaction with water vapor to obtain a series of low-NCO reactive polyurethane standard products with different hygroscopic reaction degrees, and performing infrared spectroscopy detection to obtain the absorbance of characteristic functional groups of each of the standard products;
[0012] Draw a standard curve according to the absorbance and hygroscopic reaction degree of each of the standard substances, and establish a relationship between the hygroscopic reaction degree and the absorbance;
[0013] (2) Performing infrared spectroscopy on the low NCO reactive polyurethane sample to obtain the absorbance of the characteristic functional group of the sample to be tested, and calculating the degree of hygroscopic reaction of the sample to be tested according to the relationship established in step (1).
[0014] The present invention obtains hot melt adhesive standards with different hygroscopic reaction degrees by reacting water vapor with low NCO reactive polyurethane of known isocyanate mass content, and then obtains the absorbance of characteristic functional groups by infrared spectroscopy analysis, and establishes a relationship between the hygroscopic reaction degree and the absorbance. The established method can be applied to the evaluation of the hygroscopic reaction degree of low NCO reactive polyurethane. By participating in the hygroscopic reaction with water vapor, the problem of liquid water being difficult to add to low NCO reactive polyurethane can be solved, and the problem of liquid water being difficult to disperse uniformly in hot melt adhesive can also be solved. The inventors found that low NCO reactive polyurethane is in a solid or highly viscous state at room temperature due to its low NCO content, for example, not more than 3%, and because of the large difference in polarity with water, liquid water is difficult to disperse uniformly in the sample, and water can only react locally with the sample. Direct introduction of liquid water cannot obtain a representative standard sample, and it is difficult to establish a reliable evaluation method; and the scheme of the present invention cleverly overcomes this problem. The method of the present invention can conveniently, quickly and reliably obtain the degree of hygroscopic reaction through the absorbance of characteristic functional groups of the sample to be tested, thereby providing effective information for evaluating the degree of failure of low-NCO reactive polyurethane products.
[0015] In some embodiments, in step (1), the low NCO reactive polyurethane standard is obtained by:
[0016] First, the degree of hygroscopic reaction of the standard product to be obtained is preset; that is, a series of hygroscopic reaction degrees are preset; then, the mass m2 of water required to be added for the hygroscopic reaction corresponding to the preset hygroscopic reaction degree is determined; then, the water of mass m2 is vaporized into water vapor, and the water vapor is subjected to hygroscopic reaction with the low NCO reactive polyurethane of known isocyanate mass content to obtain a series of low NCO reactive polyurethane standard products. Specifically, before preparing the standard product, the degree of hygroscopic reaction of each series of standard products is preset, and then, according to the preset hygroscopic reaction degree and the isocyanate content of the low NCO reactive polyurethane used to prepare the standard product, the mass m2 of water required to be added to the low NCO reactive polyurethane used to prepare the standard product is determined, and the water of mass m2 is vaporized into water vapor, and the water vapor is subjected to hygroscopic reaction with the low NCO reactive polyurethane used to prepare the standard product, thereby obtaining a standard product with a preset hygroscopic reaction degree. Specifically, when drawing the standard curve, it is drawn by linear fitting through the absorbance of each standard product and the preset hygroscopic reaction degree.
[0017] In some specific embodiments, the mass m2 of water required to be added for the hygroscopic reaction corresponding to the preset series of hygroscopic reaction degrees is calculated by the following formula (1):
[0018]
[0019] Wherein, X is the preset degree of hygroscopic reaction, %; that is, the degree of hygroscopic reaction of the low NCO reactive polyurethane with a known isocyanate mass content used to prepare the standard product preset in the process of establishing the standard curve;
[0020] W NCO is the mass content of isocyanate in the low NCO reactive polyurethane used for the hygroscopic reaction, %;
[0021] m1 is the mass of the low NCO reactive polyurethane used to carry out the hygroscopic reaction;
[0022] m2 is the mass of water required to be added for the hygroscopic reaction to obtain the preset hygroscopic reaction degree, that is, the mass of water required to be added for converting the low NCO reactive polyurethane with a known isocyanate mass content into a standard product with a preset hygroscopic reaction degree. Specifically, the isocyanate mass content W of the low NCO reactive polyurethane used to prepare the standard product is calculated by NCO , the mass m1 of the low NCO reactive polyurethane used to prepare the standard product and the preset hygroscopic reaction degree X are substituted into the above formula (1) to calculate the mass m2 of water required to be added to obtain the preset hygroscopic reaction degree.
[0023] The present invention can vaporize a certain amount of water into water vapor and then react with the low NCO reactive polyurethane to prepare preset standard products with different moisture absorption reaction degrees, and can establish an effective and reliable reaction degree evaluation method.
[0024] Furthermore, in step (1), the moisture absorption reaction is carried out in a closed environment; preferably, the closed environment is treated to exhaust air;
[0025] Preferably, the enclosed environment is a sealed bag or a sealed glass container; the sealed bag is preferably an aluminum foil bag or a ziplock bag, which can be sealed by a heat sealer. Such materials can be specifically selected to be able to withstand high temperatures, for example, materials with the characteristics of being able to withstand 100°C or higher, such as being able to withstand 120°C or higher, such as being able to withstand 150°C, 180°C, etc. The material of the ziplock bag is, for example, a PET / PE composite packaging bag (able to withstand 100°C), a PA / PCPP composite packaging bag (able to withstand 120-130°C), etc.; the sealed glass container withstands high temperatures, but there is a problem that air is not easily discharged. More preferably, the enclosed environment is provided by an aluminum foil bag, which has the characteristics of high heat resistance (able to withstand 180°C), easy discharge of air in the bag, and easy heat sealing. By discharging the air in the enclosed environment, the interference of environmental moisture can be avoided and the accuracy of the method can be improved.
[0026] Preferably, the temperature of the hygroscopic reaction is ≥100°C, preferably 100-110°C; below 100°C, the water in the glass tube is not completely released, and above 110°C, the sample is prone to side reactions. Carrying out the hygroscopic reaction at the preferred temperature can ensure that the liquid water is completely vaporized into water vapor and reacts with the low NCO reactive polyurethane used to prepare the standard, and can also prevent the polyurethane from cross-linking due to excessively high temperature. Using the preferred temperature conditions is conducive to improving the accuracy of the evaluation method.
[0027] Preferably, the moisture absorption reaction time is 1-3 hours.
[0028] In a preferred embodiment, before the moisture absorption reaction, the low NCO reactive polyurethane with known isocyanate mass content is spread in the closed environment to form a sample layer, and the thickness of the sample layer is preferably ≤0.5 mm. By spreading and using a preferred thickness, water vapor can be evenly diffused into the sample.
[0029] In a preferred embodiment, in step (1), the water vapor is formed by vaporizing liquid water stored in a liquid water containing element;
[0030] The liquid water in the liquid water receiving element does not come into contact with the low-NCO reactive polyurethane before being vaporized in the closed environment.
[0031] In a preferred embodiment, the liquid water containing element comprises a glass device and a water absorbing carrier placed in the inner cavity of the glass device for absorbing liquid water, wherein the glass device is provided with a water vapor outlet; preferably, the water absorbing carrier is placed in the middle of the inner cavity of the glass device. Specifically, a certain amount of water can be injected into the water absorbing carrier through a micro-injector, so that the required amount of water can be introduced.
[0032] Preferably, the water-absorbing carrier is one or more of glass wool, absorbent cotton, plastic filler, etc.; glass wool is more preferred. The inventors have found that the use of glass wool is not only convenient for filling, but also allows for more complete water release, which is conducive to further improving the accuracy and reliability of the established method.
[0033] Preferably, the glass device is a hollow glass tube; in some embodiments, the length of the hollow glass tube is 5-10 cm, more preferably 7 cm, and the inner diameter is 3-8 mm, more preferably 5 mm; the size of the hollow glass tube can be determined according to the sealing environment, such as the size of the sealing bag, so as to enable the water in the hollow glass tube to evaporate to the outside of the hollow glass tube.
[0034] In the present invention, in step (1), the sample undergoes a hygroscopic reaction, and the isocyanate radical in the system reacts with water to form a urea bond, and accordingly, in the infrared spectrum, the main functional group changes have a reduction in the stretching vibration intensity of the isocyanate radical, an increase in the stretching vibration intensity of the carbonyl group in the urea bond, and an increase in the stretching vibration intensity of NH in the urea bond. Thus, the stretching vibration of the isocyanate radical, the carbonyl group in the urea bond, the NH in the urea bond, and the absorbance of the stretching vibration of the isocyanate radical can be selected as a quantitative basis. Thus, in the present invention, the characteristic functional group can be the carbonyl group in the isocyanate radical, the urea bond, or the NH in the urea bond. Preferably, the characteristic functional group is an isocyanate radical, because in the infrared spectrum, the isocyanate radical absorption intensity is large, there is no adjacent peak interference, and after the hygroscopic reaction, the change is obvious, and a more direct corresponding relationship can be formed with the degree of hygroscopic reaction.
[0035] Preferably, the absorbance is 2200-2300cm -1 The maximum absorbance between .
[0036] In the present invention, infrared spectrum detection can be performed using an infrared spectrometer (including attenuated total reflection accessories) conventionally used in the art, such as a Nicolet NEXUS infrared spectrometer, a Bruker TENSOR II infrared spectrometer, a Thermo Fisher Nicolet iS20 infrared spectrometer, and the like.
[0037] In the present invention, the mass content of isocyanate in the low NCO reactive polyurethane is greater than 0 and less than or equal to 3%, for example, 1-3%.
[0038] In some embodiments, in step (1), the mass of the liquid water used to form the water vapor is 0.03-0.6% of the mass of the low-NCO reactive polyurethane having a known isocyanate mass content.
[0039] In some embodiments, the low NCO reactive polyurethane is a reactant obtained by reacting isocyanate with a material including alcohol and / or amine.
[0040] The technical solution provided by the present invention has the following beneficial effects:
[0041] The method of the present invention can be used to conveniently and quickly evaluate the degree of hygroscopic reaction of low NCO reactive polyurethane, providing an important basis for the quality control of low NCO reactive polyurethane. The method of the present invention obtains a standard product by reacting water vapor with low NCO reactive polyurethane, which can be applied to the evaluation of the degree of hygroscopic reaction of low NCO reactive polyurethane (especially reactive polyurethane with NCO content ≤3%), can effectively solve the problem of liquid water flowing, can realize the accurate addition of liquid water, and convert liquid water into gaseous water, which solves the problem that liquid water cannot be evenly dispersed in low NCO reactive polyurethane, can flexibly adjust the amount of water input, and can also increase the amount of water added. In a preferred embodiment, the standard product is prepared in a closed reaction environment, avoiding the interference of environmental moisture, and preventing the added water from emitting into the environment, ensuring the accurate and quantitative reaction of water and the evaluation product. The absorbance of the sample is tested by an infrared spectrometer, which is convenient and quick. By evaluating the degree of hygroscopic reaction of low NCO reactive polyurethane, the remaining amount of isocyanate in the sample can be understood, and the degree of product failure can be evaluated, which is of great significance to quality control. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a schematic diagram of inserting glass wool into a hollow glass tube in Example 1;
[0043] Figure 2 The infrared spectra of the standard products of the low NCO reactive polyurethane for fabrics in Example 1 with different degrees of moisture absorption reaction;
[0044] Figure 3 The standard curve diagram of the absorbance of isocyanate group of low NCO reactive polyurethane and the degree of hygroscopic reaction of the fabric in Example 1;
[0045] Figure 4 The infrared spectra of the standard products of the woodworking low NCO reactive polyurethane with different moisture absorption reaction degrees in Example 2;
[0046] Figure 5 The standard curve diagram of the absorbance of isocyanate and the degree of hygroscopic reaction of the woodworking low NCO reactive polyurethane in Example 2;
[0047] Figure 6 The infrared spectra of the standard products of the plastic low NCO reactive polyurethane with different moisture absorption reaction degrees in Example 3;
[0048] Figure 7 The standard curve diagram of the absorbance of isocyanate group and the degree of hygroscopic reaction of the plastic low NCO reactive polyurethane in Example 3;
[0049] Figure 8 This is the infrared spectrum of the expired plastic low-NCO reactive polyurethane product in Example 4. DETAILED DESCRIPTION
[0050] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs. Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0052] Test methods in the embodiments and comparative examples:
[0053] 1. Determination of isocyanate mass content
[0054] The mass content of isocyanate in the present invention is determined according to ASTM D2572-97 (2003) "Test Method for Isocyanate Groups in Urethane Materials or Prepolymers".
[0055] 2. Absorbance test
[0056] The testing instrument is a Nicolet infrared spectrometer (including attenuated total reflection accessories), and the instrument parameters are as follows: scanning range 4000-670cm -1 , resolution 4.0cm -1 , scan number 32. The absorbance was selected as isocyanate (2200-2300cm -1 ) Maximum absorbance.
[0057] 3. Calculation of the degree of hygroscopic reaction
[0058] The isocyanate mass percentage W of the low NCO reactive polyurethane sample used to prepare the standard product is obtained by testing the isocyanate mass content. NCO The mass of the low NCO reactive polyurethane sample for hygroscopic reaction in preparing the standard product is m1, and the degree of hygroscopic reaction of the standard product to be obtained is preset to be X. The mass of water to be added m2 can be determined by the following equation (I):
[0059]
[0060] In the following examples and comparative examples, the usability of the low NCO reactive polyurethane (low NCO reactive polyurethane) sample to be tested is judged according to the evaluation criteria shown in Table 1. Specifically, a) when the degree of hygroscopic reaction of the sample to be tested is ≤15%, it is evaluated that the bonding performance is not significantly different from that of the non-hygroscopic sample, and the sample can be used normally; b) when the degree of hygroscopic reaction is >15% and ≤20%, it is evaluated that it can be used, but the bonding performance is slightly poor. Compared with the non-hygroscopic sample, although bonding can be performed, the bonding strength is significantly reduced; c) when the degree of hygroscopic reaction is >20%, it is evaluated that it cannot be bonded to the substrate, and the sample cannot be used normally.
[0061] Table 1 Test data of moisture absorption reaction degree of low NCO reactive polyurethane
[0062] Hygroscopic reaction degree: % Application Evaluation ≤15 Can be used normally, with normal bonding performance >15 and ≤20 Can be used, but the bonding performance is slightly poor >20 Unusable, cannot be bonded
[0063] Example 1
[0064] This example is used to evaluate the degree of moisture absorption reaction of low NCO reactive polyurethane of fabric.
[0065] In this embodiment, the low NCO reactive polyurethane used is an adhesive for fabric bonding, and its NCO mass content is between 1-3%.
[0066] S1. Establishing a relationship for evaluating the degree of moisture absorption reaction of low NCO reactive polyurethane of fabric, comprising the following steps:
[0067] (1) According to ASTM D2572-97 (2003) "Test Method for Isocyanate Groups in Urethane Materials or Prepolymers", the mass content of isocyanate groups in the low NCO reactive polyurethane sample of the fabric was 2.8% (i.e., W NCO ), the low NCO reactive polyurethane sample of the fabric is used to prepare a series of standard products;
[0068] (2) 10 g (i.e., m1) of the low-NCO reactive polyurethane sample of the fabric in step (1) is used as the sample amount required for preparing one standard product. The hygroscopic reaction degree (i.e., X) of the preset series of standard products is 0%, 5%, 10%, 15%, 20%, 50%, and 80%, respectively. The above m1, X, and W are NCO Substituting into formula (I), the mass m2 of water required to prepare each preset standard with different hygroscopic reaction degree is calculated, and the corresponding masses are 0 mg, 3.0 mg, 6.0 mg, 9.0 mg, 12.0 mg, 30.0 mg, and 48.0 mg, respectively; and according to the density of water at room temperature of 1.0 g / ml, it is converted into the volume of water, which is 0 ul, 3.0 ul, 6.0 ul, 9.0 ul, 12.0 ul, 30.0 ul, and 48.0 ul, respectively;
[0069] (3) Weigh 7 portions of 10 g each of the low-NCO reactive polyurethane fabric sample prepared in step (1), and place them in 7 aluminum foil bags respectively, and spread the low-NCO reactive polyurethane fabric sample flat in the aluminum foil bags to form a sample layer (with a thickness not exceeding 0.5 mm);
[0070] (4) Prepare 7 liquid water containing elements, such as Figure 1 As shown, the element comprises a hollow glass tube (length 7 cm, inner diameter 5 mm) with both ends open, glass wool is inserted in the middle of the inner cavity of the hollow glass tube, 0ul, 3.0ul, 6.0ul, 9.0ul, 12.0ul, 30.0ul, 48.0ul of pure water are added into the glass wool of the 7 liquid water containing elements respectively by using a micro-injector, and then put into the aluminum foil bag containing the fabric low NCO reactive polyurethane sample prepared in step (3). The air in the bag is driven out and heat sealed.
[0071] (5) Place the aluminum foil bag obtained in step (4) flat on a tray in a 100° C. drying oven and react for 2 h.
[0072] (6) After cooling, 7 standard products are obtained, and then the infrared absorption spectrum of each standard product is tested using an infrared spectrometer (including attenuated total reflection accessories) (e.g. Figure 2 As shown), read isocyanate (2200-2300cm -1 )The maximum absorbance is the absorbance of isocyanate.
[0073] (7) Linearly fitting the isocyanate absorbance of each standard obtained in step (6) and the corresponding preset hygroscopic reaction degree in step (2) to draw a standard curve of hygroscopic reaction degree and isocyanate absorbance, and obtain a relationship between hygroscopic reaction degree and absorbance, such as Figure 3 shown.
[0074] S2. Verification Experiment
[0075] Using the fabric low NCO reactive polyurethane sample with an isocyanate mass content of 2.8% in step (1) of S1 as raw material, the degree of moisture absorption reaction is designed to be 15%, and the sample is treated according to the method of steps (2) to (6) of S1 to obtain a verification sample;
[0076] The infrared absorption spectrum of the test sample was read to determine the isocyanate (2200-2300cm -1) The maximum absorbance is 0.0221 (i.e., the absorbance of isocyanate), and the degree of hygroscopic reaction of the verification sample calculated according to the relationship established in step (7) of S1 is 15.2%. It can be seen that the degree of hygroscopic reaction of the verification sample (15.2%) is in good agreement with the designed degree of hygroscopic reaction (15%). It can be seen that the degree of hygroscopic reaction obtained by the evaluation method of the present invention is not significantly different from the theoretical degree of hygroscopic reaction, and has good consistency.
[0077] S3. Evaluate the hygroscopic reaction degree of the sample to be tested
[0078] A sample of the fabric low NCO reactive polyurethane was taken and infrared spectroscopy was performed according to step (6) of S1 to obtain an isocyanate absorbance of 0.0188. The degree of hygroscopic reaction of the sample was calculated to be 26.9% according to the relationship established in step (7) of S1. According to Table 1, the application evaluation was performed and it was estimated that the sample was unusable.
[0079] Apply glue to the sample to be tested and the non-moisture-absorbed sample according to the following gluing process and judge the actual performance of the sample to be tested:
[0080] First, place a piece of fabric on a flat workbench, and evenly apply the heated and melted hot melt adhesive (fabric low NCO reactive polyurethane) to the position where it needs to be pasted, then place another piece of fabric on the applied hot melt adhesive, and gently iron the fabric surface with a hot iron to bond it; then cut it into 2.5cm strips. If the strips obtained by the sample to be tested are compared with the test results of the strips obtained by the non-hygroscopic sample through the tensile test machine, and the peeling force decreases by less than 15%, it is considered that the bonding performance is normal; if the peeling force of the sample to be tested decreases by 15-30%, it is considered that the bonding performance is slightly poor; if the peeling force of the sample to be tested decreases by more than 30% or the two pieces of fabric cannot be bonded, it is considered that it cannot be used and cannot be bonded.
[0081] Through the above test, it is found that the sample to be tested in step S3 is difficult to melt by heating, and it is impossible to bond two pieces of fabric. Therefore, it can be seen that the evaluation method of the present invention can predict the product quality, and the effect is basically consistent with the actual application.
[0082] Example 2
[0083] This example is used to evaluate the degree of moisture absorption reaction of woodworking low NCO reactive polyurethane.
[0084] In this embodiment, the low NCO reactive polyurethane used is an adhesive used in the woodworking field, and the NCO mass content of the low NCO reactive polyurethane is between 1-3%.
[0085] S1: Establish a relationship to evaluate the degree of moisture absorption reaction of low NCO reactive polyurethane for woodworking
[0086] The method of step S1 of Example 1 is referred to, wherein the low NCO reactive polyurethane for woodworking is substituted for the low NCO reactive polyurethane for fabric in Example 1; in step (1), the mass content of isocyanate in the low NCO reactive polyurethane for woodworking is measured to be 2.4%; in step (2), the hygroscopic reaction degrees of the preset series of standard products are 0%, 5%, 15%, 20%, 30% and 50%, respectively, and the corresponding volumes of pure water required to be added are 0ul, 2.6ul, 7.7ul, 10.3ul, 15.4ul and 25.7ul, respectively.
[0087] In this embodiment, the infrared absorption spectrum of the obtained standard product is as follows Figure 4 As shown, the standard curve of the degree of hygroscopic reaction and the absorbance of isocyanate and the corresponding relationship are as follows Figure 5 shown.
[0088] S2. Evaluate the hygroscopic reaction degree of the sample to be tested
[0089] The sample of woodworking low NCO reactive polyurethane to be tested was subjected to infrared spectroscopy detection according to step S1 (6) in Example 1, and the isocyanate absorbance was obtained to be 0.0202. The degree of hygroscopic reaction of the sample to be tested was calculated according to the relationship established in S1 to be 10.2%. According to the application evaluation in Table 1, the product can be used normally.
[0090] Apply glue to the sample to be tested and the non-moisture-absorbed sample according to the following gluing process and judge the actual performance of the sample to be tested:
[0091] The PVC film and the board are laminated by a flat laminating machine. The amount of hot melt adhesive (woodworking low NCO reactive polyurethane, heated and melted before gluing) used is 40g / cm 2 , cut the bonded sheet into 2.5cm strips. If the strips obtained by the sample to be tested are tested by a tensile machine and the strips obtained by the sample without moisture absorption have a peeling force drop of less than 15%, the bonding performance is considered normal; if the peeling force of the sample to be tested drops by 15-30%, the bonding performance is considered slightly poor; if the peeling force of the sample to be tested drops by more than 30% or the PVC and sheet cannot be bonded, it is considered unusable and cannot be bonded.
[0092] Through the above-mentioned actual measurement, it is found that the sample to be tested in step S3 is subjected to woodworking glue application, and the bonding performance is normal.
[0093] Example 3
[0094] This example is used to evaluate the degree of moisture absorption reaction of plastic low NCO reactive polyurethane.
[0095] In this embodiment, the low NCO reactive polyurethane used is an adhesive used for bonding in the field of plastic tracks, and its NCO mass content is between 1-3%.
[0096] S1: Establish a relationship to evaluate the degree of hygroscopic reaction of plastic low NCO reactive polyurethane
[0097] The method of step S1 of Example 1 is followed, wherein the low NCO reactive polyurethane for fabric in Example 1 is replaced by a plastic low NCO reactive polyurethane sample; in step (1), the mass content of isocyanate in the plastic low NCO reactive polyurethane sample is measured to be 1.6%; in step (2), the hygroscopic reaction degrees of the preset series of standard products are 0%, 5%, 10%, 15%, 20%, 30%, and 50%, respectively, and the corresponding volumes of pure water required to be added are 0ul, 1.7ul, 3.4ul, 5.1ul, 6.9ul, 10.3ul, and 17.1ul, respectively.
[0098] In this embodiment, the infrared absorption spectrum of the obtained standard product is as follows Figure 6 As shown, the standard curve of the degree of hygroscopic reaction and the absorbance of isocyanate and the corresponding relationship are as follows Figure 7 shown.
[0099] S2. Evaluate the hygroscopic reaction degree of the sample to be tested
[0100] The sample of plastic low NCO reactive polyurethane was subjected to infrared spectroscopy detection according to step (6) of S1 in Example 1, and the isocyanate absorbance was 0.0138. The degree of hygroscopic reaction of the sample was calculated to be 6.9% according to the relationship established in S1. According to the application evaluation in Table 1, the product can be used normally.
[0101] Apply glue to the sample to be tested and the non-moisture-absorbed sample according to the following gluing process and judge the actual performance of the sample to be tested:
[0102] The binder (plastic low NCO reactive polyurethane) and rubber particles are mixed evenly in a mass ratio of 1:7, poured into a mold to prepare a sample with a thickness of 1mm, and cut into dumbbell-shaped standard samples after curing at room temperature. If the tensile strength of the standard sample obtained by the sample to be tested is tested by a tensile machine and compared with the test results of the standard sample obtained by the non-hygroscopic sample, the tensile strength decreases by less than 15%, then the bonding performance is considered normal; if the tensile strength of the sample to be tested decreases by 15-30%, then the bonding performance is considered slightly poor; if the tensile strength of the sample to be tested decreases by more than 30% or the binder and rubber particles cannot form a standard sample connected as one, it is considered unusable and cannot be bonded.
[0103] Through the above-mentioned actual measurement, it is found that the adhesive performance of the sample to be tested in step S3 is normal after the adhesive is applied.
[0104] Example 4
[0105] The performance of expired products was evaluated using the relationship established in S1 in Example 3.
[0106] The plastic low NCO reactive polyurethane product involved in this embodiment has an NCO mass content of 1.5% and a shelf life of 12 months. Two samples were stored in the workshop for 15 months and 16 months respectively, and it is not possible to determine whether the samples can be used normally. Referring to step (6) of S1 in Example 1, infrared spectroscopy detection was performed, and the infrared absorption spectra of the two samples were tested respectively, and the isocyanate (2200-2300cm -1 ) maximum absorbance, which are 0.0151 and 0.0150 respectively. The hygroscopic reaction degree of the sample to be tested is calculated according to the relationship established in step S1 of Example 3, and the hygroscopic reaction degrees of the two samples are 0.5% and 1.0% respectively. According to the application evaluation in Table 1, both samples can be used normally. Subsequently, the sample to be tested is bonded to rubber particles, and the bonding performance is not significantly different from that of the normal batch samples.
[0107] Comparative Example 1
[0108] Referring to the method in the literature "Study on Moisture Absorption Mechanism of MDI" published by Liu Hairong et al., the balance weighing method (hereinafter referred to as the weighing method) was used to evaluate the degree of moisture absorption reaction of low NCO reactive polyurethane:
[0109] The glass slide was waxed, and 200-300 mg of the same low-NCO reactive polyurethane for fabric as in step (1) of S1 in Example 1, the same low-NCO reactive polyurethane for woodworking as in step (1) of S1 in Example 2, and the same low-NCO reactive polyurethane for plastic as in step (1) of S1 in Example 3 were respectively dispersed on the glass slide, and then the glass slide was placed in a constant temperature and humidity chamber at 35° C. and 80% humidity, and the changes in the mass of the samples at different times were tracked and recorded. The results are shown in Table 2.
[0110] In Table 2, the theoretical weight loss and reaction degree at complete reaction are calculated as follows:
[0111] Through the isocyanate content test, the isocyanate mass percentage W of the low NCO reactive polyurethane (low NCO reactive polyurethane) is obtained. NCO The initial mass of the low NCO reactive polyurethane sample is m3, and the mass of the low NCO reactive polyurethane sample after the moisture absorption reaction is m4.
[0112] The theoretical weight loss M when the reaction is complete is:
[0113]
[0114] The gravimetric reaction degree X is:
[0115]
[0116] Table 2 Evaluation of the degree of moisture absorption reaction of low NCO reactive polyurethane samples by weighing method
[0117]
[0118]
[0119] The weighing method for evaluating the degree of hygroscopic reaction of low NCO reactive polyurethane is random, and the set degree of reaction cannot be obtained. This is because the following problems exist: first, the quality of water reacting with the sample cannot be controlled, and the NCO content of the low NCO reactive polyurethane sample itself is low. The weighing method cannot obtain low hygroscopic reaction degree data, and the actual low NCO reactive polyurethane often reacts with low hygroscopicity; second, in the process of carrying out this comparative example, the low NCO reactive polyurethane sample has surface crusting during the experiment, and the sample state is uneven, which cannot truly characterize the hygroscopic reaction degree of the sample. Therefore, the practical application value of the weighing method is not great, and it is difficult to monitor the product quality according to the actual production needs. It is more suitable for studying the degree of hygroscopic reaction at different times.
[0120] Comparative Example 2
[0121] The operation of S1 in Example 1 is referred to, except that in step (4), no hollow glass tube is used, but water is directly applied to the flat fabric low-NCO reactive polyurethane sample. Other operations are the same as in Example 1.
[0122] During the operation, it was found that after the sample was reacted in a drying oven at 100°C for 2 hours, the viscosity was locally too high, and the unevenness of the sample made it impossible to carry out subsequent operations. This is because the water has a high reaction activity with the isocyanate in the sample, and it can react at room temperature. As the temperature rises, the reaction activity increases. During the heating process, the water is not completely vaporized, and urea substances have already formed with the local sample. The urea substances have poor compatibility with the sample and cannot be evenly dispersed in the sample. Therefore, the method of directly adding water to the sample is not feasible.
[0123] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A method for evaluating the degree of hygroscopic reaction of low NCO reactive polyurethane, characterized in that: The method comprises the following steps: (1) subjecting a low-NCO reactive polyurethane having a known isocyanate mass content to a hygroscopic reaction with water vapor to obtain a series of low-NCO reactive polyurethane standard products with different hygroscopic reaction degrees, and performing infrared spectroscopy detection to obtain the absorbance of characteristic functional groups of each of the standard products; Draw a standard curve according to the absorbance and hygroscopic reaction degree of each of the standard substances, and establish a relationship between the hygroscopic reaction degree and the absorbance; (2) Performing infrared spectroscopy on the low NCO reactive polyurethane sample to obtain the absorbance of the characteristic functional group of the sample to be tested, and calculating the degree of hygroscopic reaction of the sample to be tested according to the relationship established in step (1).
2. The method according to claim 1, characterized in that In step (1), the low NCO reactive polyurethane standard is obtained by the following method: Preset the degree of hygroscopic reaction of the standard product to be obtained, determine the mass m2 of water required to be added for the hygroscopic reaction corresponding to the preset degree of hygroscopic reaction, vaporize the mass m2 of water into water vapor, and make the water vapor react with the low-NCO reactive polyurethane with known isocyanate mass content to obtain a series of the standard products; The standard curve is drawn by fitting according to the absorbance of each standard and the preset hygroscopic reaction degree.
3. The method according to claim 2, characterized in that The mass m2 is specifically calculated by the following formula (1): Wherein, X is the preset degree of hygroscopic reaction, %; W NCO is the mass content of isocyanate in the low NCO reactive polyurethane used for the hygroscopic reaction, %; m1 is the mass of the low NCO reactive polyurethane used to carry out the hygroscopic reaction; m2 is the mass of water required to be added to carry out the hygroscopic reaction to obtain the preset hygroscopic reaction degree.
4. The method according to any one of claims 1 to 3, characterized in that: In step (1), the moisture absorption reaction is carried out in a closed environment; preferably, the closed environment is treated to exhaust air; Preferably, the sealed environment is a sealed bag or a sealed glass container; the sealed bag is preferably an aluminum foil bag or a ziplock bag.
5. The method according to claim 4, characterized in that The temperature of the moisture absorption reaction is ≥100°C, preferably 100-110°C; Preferably, the moisture absorption reaction time is 1-3 hours.
6. The method according to claim 4, characterized in that Before the moisture absorption reaction is carried out, the low-NCO reactive polyurethane with known isocyanate mass content is spread in the closed environment to form a sample layer, and preferably the thickness of the sample layer is ≤0.5 mm.
7. The method according to claim 4, characterized in that In step (1), the water vapor is formed by vaporizing liquid water stored in a liquid water containing element; The liquid water in the liquid water receiving element does not come into contact with the low-NCO reactive polyurethane before being vaporized in the closed environment.
8. The method according to claim 7, characterized in that The liquid water containing element comprises a glass device and a water absorbing carrier placed in the inner cavity of the glass device for absorbing liquid water, and the glass device is provided with a water vapor outlet; preferably, the water absorbing carrier is placed in the middle of the inner cavity of the glass device; Preferably, the water-absorbing carrier is one or more of glass wool, absorbent cotton, and plastic filler; Preferably, the glass device is a hollow glass tube, and preferably the hollow glass tube has a length of 5-10 cm and an inner diameter of 3-8 mm.
9. The method according to any one of claims 1 to 3, characterized in that: The characteristic functional group is an isocyanate group, a carbonyl group in a urea bond, or an NH group in a urea bond, preferably an isocyanate group; Preferably, the absorbance is 2200-2300cm -1 The maximum absorbance between .
10. The method according to any one of claims 1 to 9, characterized in that: The mass content of isocyanate in the low NCO reactive polyurethane is greater than 0 and less than or equal to 3%, preferably 1-3%; And / or, in step (1), the mass of liquid water used to form the water vapor is 0.03-0.6% of the mass of the low-NCO reactive polyurethane with a known isocyanate mass content; And / or, the low NCO reactive polyurethane is a reactant obtained by reacting isocyanate with a material including alcohol and / or amine.
Citation Information
Patent Citations
Method for detecting contents of moisture and / or urea in isocyanate, and application of same to on-line monitoring
CN107703096A